In vitro Antifungal Activity of Olive (Olea europaea) Leaf Extracts Loaded in Chitosan Nanoparticles - Muzzalupo, Innocenzo; Badolati, Giuliana; Chiappetta, Adriana; Picci, Nevio; Muzzalupo, Rita (Frontiers in Bioengineering and Biotechnology, 2020)
Olive leaf extract is characterized by a high content of phenols and flavonoids (oleuropein, luteolin and their derivatives). These compounds are defined as secondary metabolites and exert such as anti-inflammatory, antioxidant, and antimicrobial activities. We investigated the in vitro antifungal activity of two olive leaf extracts (named EF1 and EF2) against a Fusarium proliferatum (AACC0215) strain that causes diseases to many economically important plants and synthesizing diverse mycotoxins. In this work, we aimed to identify the most appropriate concentration between the tested two olive leaf extracts to develop a safe, stable and efficient drug delivery system. Qualitative and quantitative analyses of the two olive leaf extracts by (HPLC) were performed. Furthermore, we also evaluated the antifungal effects of the two leaf extracts when encapsulated in chitosan-tripolyphosphate nanoparticles. The major compound in both EF1 and EF2 was oleuropein, with 336 mg/g and 603 mg/g respectively, however high concentrations of flavonoid were also present. EF1 and EF2 showed a concentration depended effect on F. proliferatum (AACC0215) viability. Our results showed a great efficacy of EF1/nanoparticles at the higher concentration tested (12X) against the target species. In this case, we observed an inhibition rate to both germination and growth of 87.96% and 58.13%, respectively. We suggest that EF1 olive leaf extracts, as free or encapsulated in chitosan-tripolyphosphate nanoparticles, could be used as fungicides to control plant diseases. Finally, future application of these findings may allow to reduce the dosage of fungicides potentially harmful to human health.